From research to reality: digital parent training for managing disruptive behaviour in children - Ristkari, Terja; Kinnunen, Malin; Kurki, Marjo (Edward Elgar Publishing, 2026)
Behavioural problems in early childhood pose a significant public health concern, often going undetected in primary care settings. Early identification and evidence-based interventions are crucial to addressing long-term impacts on children, families, and society. Voimaperheet is a Finnish model that integrates early screening with a digitally assisted parent training programme tailored for primary healthcare. The programme aims to enhance parenting skills and prevent the escalation of children's disruptive behaviour, offering an effective and preventive approach. The Voimaperheet model has demonstrated effectiveness through randomised controlled trials and implementation research and by the benefits of digital delivery in broadening access to mental health services. By successfully integrating the Voimaperheet model into routine care, it can be illustrated how validated approaches like Voimaperheet can contribute to sustainable public health policies and support broader social investment frameworks.
Beyond the Nordic Welfare State – Extending Social Investments with Interventions